Simplified TBA equations of the AdS_5 x S^5 mirror model - FROLOV, SERGEY (IOP Publishing, 2009)
We use the recently found integral representation for the dressing phase in the kinematic region of the mirror theory to simplify the TBA equations for the AdS5 ? S5 mirror model. The resulting set of equations provides an efficient starting point for both analytic and numerical studies.
PUBLISHED
Keywords: Computational physics; Particle physics and field theory